Factors Influencing Purchase Decision Super Air Jet Tickets at International Airport Soekarno-Hatta - Rut Monica; Maryana Refo; Reni Dian Octavian; Cut Keumala (Jurnal Ilmu Multidisiplin, 2025)
After the COVID-19 pandemic subsided in 2022, Indonesia's aviation sector began to rise, as seen by the increase in passenger numbers. Super Air Jet, a new airline with a low-cost carrier concept, emerged and targeted millennials and generation Z who have an active lifestyle and love to travel. This study aims to analyse the influence of lifestyle, web quality, and convenience on Super Air Jet ticket purchasing decisions. The method used is a quantitative approach with analysis using SMARTPLS (Partial Least Square) version 4.0, involving 160 respondents as a sample. Data was obtained through distributing questionnaires using the non-probability sampling method of accidental sampling (convenience sampling). The results showed that all variables had a significant effect on purchasing decisions. It is recommended that Super Air Jet continue to improve customer service and accessibility to attract more consumers in an increasingly competitive aviation market.